Exact Decoding Probability Under Random Linear Network Coding - Trullols-Cruces, O; Barcelo-Ordinas, J M; Fiore, M (IEEE communications letters, 2011)
In this letter, we compute the exact probability that a receiver obtains N linearly independent packets among K ≥ N received packets, when the sender/s use/s random linear network coding over a Galois Field of size q. Such condition maps to the receiver's capability to decode the original information, and its mathematical characterization helps to design the coding so to guarantee the correctness of the transmission. Our formulation represents an improvement over the current upper bound for the decoding probability, and provides theoretical grounding to simulative results in the literature.